Dysgeusia in cancer patients undergoing radiotherapy: etiology, diagnosis and therapy - Andrade, Camila Lima; Dantas, Juliana Borges de Lima; Melo, Amanda de Sousa; Medrado, Alena Ribeiro Alves Peixoto; Martins, Gabriela Botelho; Lima, Hayana Ramos; Carrera, Manoela (Journal of Oral Diagnosis, 2019)
Introduction: The diagnosis of cancer can provoke innumerable changes in the life of cancer patients, caused by the illness and the methods of treatment. Dysgeusia is a common complication, which directly affects the nutritional status causing loss of appetite and decreased intake. Aim: The present paper presents a review of the etiology, diagnosis, and treatment of this oral complication. Material and methods: The present literature review selected articles based on the titles that addressed dysgeusia in cancer patients, as well as the etiology, diagnosis and treatment. After previous analysis, we included 31 relevant articles on the proposed theme. Results: Dysgeusia can be a symptom or a common consequence of several causes. Radiation therapy may lead to dysgeusia, altering the structure of the pores of the palate or causing a thinning of the epithelium of the papilla. The exact mechanism of dysgeusia in cancer patients is not well elucidated. The diagnosis of dysgeusia can be obtained through objective and subjective methods. The objective methods used are chemical gustometria and electrogustometria. The subjective analysis can be performed through questionnaires where patients report if they noticed changes in taste in the foods consumed daily. Various types of treatments are being used to improve taste disorders, such as zinc supplementation, alpha-lipoic acid (ALA), ginkgo biloba, pilocarpine, transcranial magnetic stimulation, and acupuncture. Final considerations: The studies are still inconclusive regarding the etiology of the disease and the treatment methods that reduce the impact of dysgeusia on the life of cancer patients.